Relative pitch: encouraging performance in public space - Smith, Daniel Elias (Kansas State University, 2011)
Street musicians and performers attract people to public spaces. These performers, or ‘buskers’ as they are commonly referred, typically congregate along specific streets, parks, plazas, and transit stops in a city. The term pitch describes the place buskers perform. Pedestrian flow, visibility, and acoustics are just some of the factors that street performers consider when selecting a pitch. While performers resourcefully adapt to the challenges of different pitches, public spaces often do little to accommodate performers and their audiences. William Whyte observed how street performances facilitate social interactions between strangers and give character to cities and neighborhoods. Relative Pitch explores where performances occur and how they benefit public places. Case studies of popular busking locations establish a typology of squares, streets, and transit stops. Video clip analysis of street performances demonstrates the spatial relations between performer and audience. Dimensions and observations from these case studies provided insight and information for the application of the typology to proposed sites in Wichita, Kansas. Buskers adapt pitches relative to their physical environment. Point, linear, planar, and volumetric elements define and articulate temporary stages, audience space, and circulation paths during performances. Design proposals for the typology sites in Wichita illustrate how flexible performance spaces can be incorporated in squares, streets, and transit stops. This project looks at ways to activate public spaces by encouraging street performance.
Keywords: Street Performer; Busker; Street Musician; Public Space; William Whyte; Wichita, Kansas; Landscape Architecture (0390)